Physical Properties and Safety of 100% Post-Consumer Pet Bottle -Organoclay Nanocomposites Towards a Circular Economy - Guarda-Moraga, A; Valenzuela-Bascunan, X; Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A; Garrido-Ayala, L; Velasquez, E (Elsevier B.V., 2020)
Polyethylene terephthalate from bottle waste (RPET) was compounded with an organically modified nanoclay at increasing concentrations by extrusion to improve its physical-mechanical properties. Nanocomposites evidenced combined intercalated/tactoid structures by XRD and TEM. The higher tactoid proportion increased the color variation and the opacity of the films but did not affect the transparency. Although clay addition did not affect the thermal properties of PET samples, crystallinity and the barrier effect against volatile release increased with clay concentration. The elastic modulus of nanocomposites was higher than control RPET film. Mechanical parameters of RPET film with 5 wt% of organoclay were similar to those obtained from virgin polymer (PET). Global migration and metal traces migration from nanocomposite films to food simulants were below current European Union legislation. © 2020 Elsevier B.V.